A Recreational Boater-Based Method for Re-designing the NOS Small-Craft Chart - Gustavo Antonini; Niels West; Charles Sidman; Robert Swett (EDIS)
New to EDIS! TP-107, a 145-page illustrated project report by Gustavo Antonini, Niels West, Charles Sidman, and Robert Swett, reports on a project to determine chart information which would satisfy criteria for safe, modern navigation and promote environmental stewardship. The prototype chart covers the southwest Florida coast from lower Tampa Bay to Charlotte Harbor. Published by the Florida Sea Grant Program, December 2000. Reviewed March 2008.